Microstructure and property evolution of Cu–9Ni–6Sn-xCr alloys during thermo-mechanical treatment process - Yuanqi You; Caiju Li; Kui Jin; Jiangnan Li; Qiong Lu; Zunyan Xu; Peng Gao; Xuhui Xu; Fengxian Li; Jianhong Yi (Journal of Materials Research and Technology, 2024)
In this study, Cu–9Ni–6Sn-xCr alloys (x = 0, 0.3, 0.6, or 1.0) were designed and prepared. The influence of Cr content on the microstructure, the precipitation behavior, and the mechanical properties of the alloys was systematically investigated. The results show that the Cu–9Ni–6Sn-0.6Cr alloy exhibits outstanding mechanical properties and higher level electrical conductivity after aging at 400 °C for 8 h: The peak-aged hardness reaches 323.6 ± 8.4 HV, with a tensile strength of 876.4 MPa and an electrical conductivity of 12.59 ± 0.33% IACS. These excellent comprehensive properties of Cu–9Ni–6Sn-0.6Cr alloy are attribute to the refinement effect and the precipitation of DO22 phase within the Cu matrix grains. Further analysis reveals that the addition of an appropriate amount of Cr refines the microstructure of the alloy and promotes the precipitation of the DO22 phase. At the same time, Cr also suppresses the precipitation of the DO3 phase at grain boundaries, achieving an excellent combination of plasticity, electrical conductivity, and strength. This work suggests that the potential application prospects of Cr in the multi-component design of Cu–Ni–Sn alloy, and the addition of 0.6 wt% Cr can achieve good strengthening effects and provide outstanding comprehensive performance for Cu–Ni–Sn alloys.